Analisis Faktor-Faktor yang Berpengaruh terhadap Sikap Pengguna Aset Digital Non-Fungible Token Berbasis Blockchain pada Komunitas NFT Indonesia - Muhamad Ramdani, Risma; Sumarwan, Ujang; Hermadi, Irman (Jurnal Manajemen dan Organisasi, 2023)
Blockchain is an inspiring new technology that requires a lot of attention from various researchers and companies. This technology offers various benefits, where the newest derivative of this technology is Non-Fungible Tokens (NFT). In NFT, various digital assets such as images, videos, music or virtual creations are traded. The relatively new NFT creates a lack of user knowledge to be able to utilize this technology as a digital asset for trading. On the one hand, users welcome the use of NFTs as a tool to gain financial gain, but on the other hand, there are users who doubt the long-term success of NFTs as a form of investment and see them as a temporary trend that may be detrimental in the event of a market crash. The purpose of this research is to explore various factors that can impact the attitudes of NFT users. The research used a quantitative method which was carried out at the Indonesian NFT Community, involving 377 respondents as a sample. Questionnaires were distributed online using the Google form on the Telegram platform. The data analysis used in this research is by using Structural Equation Modeling (SEM). The results of the study show that there are five factors that significantly influence the attitude of NFT users. Perceived ease of use, perceived usefulness, perceived trust, and personal innovativeness have a positive and significant effect on user attitudes, while perceived risk has a negative effect and is one of the factors that has the most impact on user attitudes than other factors, followed by perceived trust in the second position as the most dominant variable. So like any new technology, NFTs have risks and trust issues that most users consider.